(untitled) (Academicia Globe: Inderscience Research, 2022)
Steel is one of the largest and oldest materials used in all engineering applications. Steel is used in construction, in industries, in machineries, in plants etc. The aim of providing steel in appropriate form is to strengthen the particula member. Hence we can conclude that apart from the oldest material steel is having the characteristic which will help in enhancing the strength of the member. If provided steel is of appropriate quality as well as of quantity it will give the strength to the member till its expected life span. But before having faith on provided steel directly its necessary to take care for the health of steel we are providing, as there are lots of risk, if we won’t handle them properly it will collapse all the assumed strength as well as expected service life span of the member. The most important risk to steel is from corrosion. In this review it is tried to address the different research work done so far related to corrosion. Review takes account of corrosion phenomenon - deteriorating the strength of materials, it’s types and effect on weakening of the affected material. Also the method of tackling corrosion resistant such as by coatings on materials. Study of conditions leading to the kind of corrosion developed. Use of different coating materials and their performance. Review of effect of polarization resistance on corrosion rate of zinc with an increase in the degree of deformation, forming behavior of coated steel sheets. Effect of coating type, coating thickness etc. on the forming limit strains, strain distribution, interface friction coefficient variation, lubrication characteristics, surface roughening, wear behavior etc. and also the testing methods of coating is reviewed in this research paper.